Solid electrolyte, preparation method thereof and solid-state battery

By using gel to coat the first fiber fabric in the solid electrolyte, the ion transport capability and mechanical strength of the gel electrolyte under liquid lean conditions are improved, and the problems of low ion transport capability and safety hazards in the prior art are solved.

CN119764542AActive Publication Date: 2025-04-04CHINA TELECOM CORP LTD TECHNOLOGY INNOVATION CENTER +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411897327.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-04
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The existing gel electrolyte has low ion transport capacity under liquid lean conditions and insufficient mechanical strength, making it difficult to resist the growth of lithium dendrites, which poses safety risks.

Method used

The solid electrolyte including a gel and a first fiber fabric is adopted, and the gel is coated with the first fiber fabric, the first fiber includes polyvinylidene fluoride fiber, and the second fiber includes polypropylene carbonate fiber, and the electrolyte content is controlled between 5% and 10% to achieve an improvement in ion transport capacity.

Benefits of technology

It improves the ion transport capability of solid electrolyte under liquid lean conditions, enhances mechanical strength, reduces the electrolyte content, improves safety, and avoids the growth of lithium dendrites.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764542A_ABST
    Figure CN119764542A_ABST
Patent Text Reader

Abstract

The invention discloses a solid electrolyte, a preparation method thereof and a solid-state battery. The solid electrolyte comprises gel and a first fiber fabric, the first fiber fabric is coated with the gel, and pores of the first fiber fabric are filled with the gel; the first fiber fabric comprises first fibers formed by interweaving, and a forming material of the gel comprises an electrolyte and second fibers dissolved in the electrolyte; wherein the first fibers comprise polyvinylidene fluoride fibers, and the second fibers comprise polypropylene carbonate fibers. The ion transmission capability of the solid electrolyte under the barren solution condition can be improved, and the safety is relatively high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of energy storage and power batteries, and in particular to a solid electrolyte and a preparation method thereof, and a solid-state battery. Background Art

[0002] Solid-state batteries use solid electrolytes. The polymer electrolytes in solid electrolytes have advantages such as good interface contact and strong processability, but their ion transmission capacity is poor and their ion conductivity is low. The gel electrolyte obtained by absorbing the electrolyte in the polymer electrolyte has both the safety of solid electrolytes and the high ion conductivity of liquid electrolytes. However, the electrolyte content in the gel electrolyte usually exceeds 50% of the mass of the polymer matrix. The high electrolyte content will bring safety hazards, and the gel electrolyte itself has poor mechanical strength and is difficult to resist the growth of lithium dendrites. If the content of electrolyte in the gel electrolyte is reduced, the ion transmission efficiency will be limited. Therefore, there is an urgent need for a technology to improve the ion transmission capacity of gel electrolytes under lean conditions. Summary of the invention

[0003] The present application discloses a solid electrolyte and a preparation method thereof, and a solid-state battery, which can improve the ion transmission capacity of the solid electrolyte under lean liquid conditions and have high safety.

[0004] In order to achieve the above objectives, this application provides the following technical solutions:

[0005] In a first aspect, the present application provides a solid electrolyte, including a gel and a first fiber fabric;

[0006] The gel covers the first fiber fabric and fills the pores of the first fiber fabric;

[0007] The first fiber fabric includes interwoven first fibers, and the gel-forming material includes an electrolyte and second fibers dissolved in the electrolyte; wherein the first fibers include polyvinylidene fluoride fibers, and the second fibers include polypropylene carbonate fibers.

[0008] The above-mentioned solid electrolyte includes a gel and a first fiber fabric, the gel coats the first fiber fabric and fills the pores of the first fiber fabric. The first fiber fabric includes a first fiber interwoven, and the forming material of the gel includes an electrolyte and a second fiber dissolved in the electrolyte. Among them, the first fiber includes polyvinylidene fluoride fiber, and the second fiber includes polypropylene carbonate fiber. In the present application, the first fiber serves as a rigid skeleton support, and the second fiber is dissolved in the electrolyte and coated on the surface of each first fiber to form a gel-state ion transport network, creating conditions for electronic conduction and improving the ion transmission capacity. At the same time, the structure of the gel-coated first fiber fabric of the solid electrolyte in the present application can make the distribution of the second fiber more uniform, which is conducive to reducing the amount of electrolyte used, and is conducive to realizing the depletion of the solid electrolyte, and ensuring safety during use.

[0009] In some embodiments, in the solid electrolyte, the mass of the electrolyte accounts for 5%-10% of the sum of the mass of the first fiber and the second fiber.

[0010] In some embodiments, the solid electrolyte further includes fluorinated boron nitride, and the fluorinated boron nitride is dispersed in the gel.

[0011] In some embodiments, the mass of the fluorinated boron nitride accounts for 10% to 60% of the mass of the second fiber.

[0012] In some embodiments, the electrolyte includes a non-aqueous organic solvent, a lithium salt, and an additive.

[0013] In some embodiments, the non-aqueous organic solvent includes cyclic carbonates and linear carbonates.

[0014] In a second aspect, the present application provides a method for preparing a solid electrolyte, comprising:

[0015] Providing a second fiber fabric, the second fiber fabric comprising first fibers and second fibers interwoven; wherein the first fibers comprise polyvinylidene fluoride fibers, and the second fibers comprise polypropylene carbonate fibers;

[0016] The electrolyte is dripped onto the second fiber fabric, and the second fibers are dissolved in the electrolyte to form a gel covering the first fibers, thereby obtaining the solid electrolyte.

[0017] In some embodiments, the second fiber fabric is provided, wherein the second fiber fabric includes first fibers and second fibers interwoven together, and the method further includes:

[0018] The first electrospinning liquid and the second electrospinning liquid are prepared to form the second fiber fabric by adopting an electrostatic spinning process; wherein the first electrospinning liquid includes a polyvinylidene fluoride solution, and the second electrospinning liquid includes a polypropylene carbonate solution.

[0019] In some embodiments, the second electrospinning solution further includes a boron nitride fluoride solution, and when the electrolyte is dripped onto the second fiber fabric, the boron nitride fluoride is dispersed in the gel.

[0020] In a third aspect, the present application provides a solid-state battery, comprising a positive electrode active material, a negative electrode active material and a solid electrolyte as described in the first aspect. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 A schematic diagram of the structure of a solid electrolyte provided in an embodiment of the present application;

[0022] Figure 2 A schematic diagram of the structure of another solid electrolyte provided in an embodiment of the present application;

[0023] Figure 3 A schematic flow chart of a method for preparing a solid electrolyte provided in an embodiment of the present application;

[0024] Figure 4 A schematic diagram of the structure of a second fiber fabric provided in an embodiment of the present application;

[0025] Figure 5 A schematic diagram of the structure of another second fiber fabric provided in an embodiment of the present application;

[0026] Figure 6 A schematic diagram of the structure of another second fiber fabric provided in an embodiment of the present application;

[0027] Figure 7 A schematic diagram of the structure of another second fiber fabric provided in an embodiment of the present application;

[0028] Figure 8 A schematic diagram of the structure of another second fiber fabric provided in an embodiment of the present application;

[0029] Fig. 9 A schematic diagram of the structure of another second fiber fabric provided in an embodiment of the present application;

[0030] Fig.10 A schematic flow chart of a method for preparing a second fiber fabric provided in an embodiment of the present application;

[0031] Fig.11 A schematic diagram of the structure of a solid-state battery provided in an embodiment of the present application;

[0032] Fig.12 A schematic diagram of a solid-state battery preparation process provided in an embodiment of the present application;

[0033] Icons: 1. Gel; 11. Second fiber; 2. First fiber fabric; 21. First fiber; 3. Boron nitride fluoride; 4. Battery cell. DETAILED DESCRIPTION

[0034] The following will combine the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application. Among them, in the description of the embodiments of the present application, unless otherwise specified, " / " means or, for example, A / B can mean A or B; "and / or" in the text is only a description of the association relationship of associated objects, indicating that there can be three relationships, for example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. In addition, in the description of the embodiments of the present application, "multiple" refers to two or more than two.

[0035] The terms "first" and "second" are used for descriptive purposes only and should not be understood as suggesting or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the embodiments of the present application, unless otherwise specified, "multiple" means two or more.

[0036] First, as Figure 1-Figure 2 As shown, an embodiment of the present application provides a solid electrolyte, including a gel 1 and a first fiber fabric 2;

[0037] The gel 1 covers the first fiber fabric 2 and fills the pores of the first fiber fabric 2;

[0038] The first fiber fabric 2 includes interwoven first fibers 21, and the forming material of the gel 1 includes an electrolyte and second fibers dissolved in the electrolyte; wherein the first fibers 21 include polyvinylidene fluoride fibers, and the second fibers include polypropylene carbonate fibers.

[0039] The above-mentioned solid electrolyte includes a gel 1 and a first fiber fabric 2, wherein the gel 1 coats the first fiber fabric 2 and fills the pores of the first fiber fabric 2. The first fiber fabric 2 includes interwoven first fibers 21, and the forming material of the gel 1 includes an electrolyte and a second fiber dissolved in the electrolyte. Among them, the first fiber 21 includes polyvinylidene fluoride fibers, and the second fiber includes polypropylene carbonate fibers. In the present application, the first fiber 21 serves as a rigid skeleton support, and the second fiber is dissolved in the electrolyte and coated on the surface of each first fiber 21 to form a gel-state ion transport network, creating conditions for electronic conduction and improving ion transmission capacity. At the same time, the structure of the gel 1 coating the first fiber fabric 2 of the solid electrolyte in the embodiment of the present application can make the distribution of the second fiber more uniform, which is conducive to reducing the amount of electrolyte used, and is conducive to achieving the depletion of the solid electrolyte, and ensuring safety during use.

[0040] In some embodiments, the mass of the electrolyte in the solid electrolyte accounts for 5%-10% of the sum of the mass of the first fiber 21 and the second fiber, for example, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, etc., and the specific mass percentage is not limited.

[0041] The embodiment of the present application uses a trace amount of electrolyte to achieve liquid absorption and dissolution of the second fiber and surface coating of the first fiber 21, which greatly reduces the content of electrolyte in the solid electrolyte, is beneficial to improving ion transmission efficiency, improving safety of use, and greatly reducing safety hazards.

[0042] In some embodiments, the solid electrolyte further includes fluorinated boron nitride (F-BN) 3, and the fluorinated boron nitride 3 is dispersed in the gel.

[0043] One possible way to achieve this is as follows: Figure 2 As shown, the fluorinated boron nitride 3 as a filler is uniformly dispersed in the gel 1. Since the gel 1 is coated on the surface of each first fiber 21, the fluorinated boron nitride 3 also coats each first fiber 21, thereby achieving uniform distribution of the fluorinated boron nitride 3.

[0044] When the solid electrolyte of the embodiment of the present application is applied to a lithium-ion battery, the fluorinated groups in the fluorinated boron nitride 3 and the N in BN are involved in the film formation on the surface of the battery electrode, generating an inorganic component containing LiF / Li3N, stabilizing the electrode interface, and helping to improve the cycle stability of the battery. At the same time, the fluorinated boron nitride 3 has the characteristics of high thermal conductivity and high Young's modulus, which is conducive to the uniform dispersion of heat inside the solid electrolyte, thereby inhibiting the growth of lithium dendrites in local temperature hot spots. Since the fluorinated boron nitride 3 participates in the electrode interface reaction, its product is also conducive to the efficient and uniform transmission of ions, further ensuring that the battery has good electrochemical properties. The structure of the gel 1 coating the first fiber fabric 2 of the solid electrolyte of the embodiment of the present application, and the synergistic effect of the fluorinated boron nitride 3 filler, can achieve the depletion of the solid electrolyte, and after being applied to the battery, the high safety and high performance operation of the battery can be achieved.

[0045] In some embodiments, the mass of the fluorinated boron nitride 3 accounts for 10%-60% of the mass of the second fiber, for example, 10%, 12%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, etc., and the specific mass proportion is not limited.

[0046] According to the actual application situation, the mass proportion of boron nitride fluoride 3 can be reasonably adjusted so that boron nitride fluoride 3 is evenly dispersed in the gel of the solid electrolyte, which can effectively inhibit the growth of lithium dendrites in lithium-ion batteries and facilitate efficient and uniform ion transmission.

[0047] In some embodiments, the electrolyte includes a non-aqueous organic solvent, a lithium salt and an additive, wherein the additive includes fluoroethylene carbonate (FEC), propylene sulfite (PS), propylene sulfite (PST), diethyl sulfate (DTD) and the like.

[0048] In some embodiments, the non-aqueous organic solvent includes cyclic carbonate and linear carbonate. The embodiment of the present application utilizes the principle that polypropylene carbonate (PPC) is similarly compatible with ester electrolytes. After the electrolyte is added, polypropylene carbonate (PPC) is dispersed into a gel state and coated together with fluorinated boron nitride (F-BN) on the surface of the interwoven skeleton formed by polyvinylidene fluoride (PVDF) fibers to form a continuous ion transport network for ion transport.

[0049] Second, as Figure 3 As shown, the present invention provides a method for preparing a solid electrolyte, which specifically includes the following steps:

[0050] S301, providing a second fiber fabric, the second fiber fabric comprising first fibers and second fibers interwoven; wherein the first fibers comprise polyvinylidene fluoride fibers, and the second fibers comprise polypropylene carbonate fibers;

[0051] S302, dripping an electrolyte onto the second fiber fabric, the second fibers are dissolved in the electrolyte and form a gel covering the first fibers, to obtain a solid electrolyte.

[0052] In the above S301, the interweaving forms of the first fibers and the second fibers in the second fiber fabric can be various. Figure 4 As shown, a first fiber 21 and a second fiber 11 are first arranged side by side to form a mixed fiber, and then a plurality of fibers are interwoven horizontally and vertically to form a second fiber fabric.

[0053] For example, Figure 5 As shown, a first fiber 21 and two second fibers 11 are first arranged side by side to form a mixed fiber, and the two second fibers 11 are located on both sides of the first fiber, and then multiple fibers are interwoven horizontally and vertically to form a second fiber fabric.

[0054] For example, Figure 6 As shown, two first fibers 21 and one second fiber 11 are first arranged side by side to form a mixed fiber, and the two first fibers 21 are located on both sides of the second fiber 11, and then multiple fibers are interwoven horizontally and vertically to form a second fiber fabric.

[0055] For example, Figure 7 As shown, two first fibers 21 and two second fibers 11 are first arranged side by side to form a mixed fiber, and the first fibers 21 and the second fibers 11 are arranged in an interlaced manner, and then multiple fibers are interlaced horizontally and vertically to form a second fiber fabric. Of course, a mixed fiber can also include multiple first fibers 21 and multiple second fibers 11 arranged in an interlaced manner.

[0056] For example, Figure 8 As shown, a first fiber 21 and a second fiber 11 are directly interwoven horizontally and vertically to form a second fiber fabric, and the first fiber 21 is horizontal and the second fiber 11 is vertical. Fig. 9 As shown, a first fiber 21 and a second fiber 11 are directly interwoven horizontally and vertically to form a second fiber fabric, and both the first fiber 21 and the second fiber 11 have horizontal and vertical directions, and the two are arranged alternately.

[0057] It is understood that the distribution forms of the first fibers 21 and the second fibers 11 can be various to ensure that after the electrolyte is dripped in, the gel 1 formed by the second fibers 11 dissolving in the electrolyte can achieve the following: Figure 1 It is sufficient to uniformly cover each first fiber as shown.

[0058] In the above S302, the electrolyte is dripped onto the second fiber fabric, and the second fiber is dissolved in the electrolyte to form a gel covering the first fiber. It can be understood that at this time, the fiber fabric is the first fiber fabric (the first fibers are interwoven), and in the solid electrolyte after the coating, the gel may not completely fill the pores of the first fiber fabric, but the gel covers each first fiber as much as possible to form a continuous ion transmission network for ion transport.

[0059] In some embodiments, Fig.10 As shown, a second fiber fabric is provided, the second fiber fabric includes first fibers and second fibers interwoven, and also includes:

[0060] S1001. Use an electrospinning process to prepare a second fiber fabric from a first electrospinning liquid and a second electrospinning liquid; wherein the first electrospinning liquid includes a polyvinylidene fluoride solution, and the second electrospinning liquid includes a polypropylene carbonate solution.

[0061] The embodiment of the present application adopts an electrospinning process to prepare the second fiber fabric, which is beneficial to improving the distribution uniformity of the dissolved second fibers and improving the ion conductivity, thereby helping to reduce the amount of electrolyte used and ensure high performance and high safety.

[0062] In some embodiments, the second electrospinning solution further includes a boron nitride fluoride solution, and when the electrolyte is dripped onto the second fiber fabric, the boron nitride fluoride is dispersed in the gel.

[0063] In order to improve the mechanical strength of the solid electrolyte and resist the growth of lithium dendrites, the embodiment of the present application adds an appropriate amount of fluorinated boron nitride to the second electrospinning solution, and forms a second fiber together with polypropylene carbonate during the electrospinning process. After the electrolyte is added, polypropylene carbonate is dispersed into a gel state, and together with fluorinated boron nitride, it is coated on the surface of the interwoven skeleton formed by the polyvinylidene fluoride fiber to form a continuous ion transport network for ion transport. When the solid electrolyte is applied to a battery, it is beneficial to improve the cycle performance of the battery.

[0064] In a third aspect, an embodiment of the present application provides a solid-state battery, comprising a positive electrode active material, a negative electrode active material, and a solid electrolyte as in the first aspect. The positive electrode active material may be lithium iron phosphate, and the negative electrode active material may be lithium metal. Fig.11 As shown, the solid-state battery may include a plurality of battery cells 4 .

[0065] In order to make the solution provided in the embodiments of the present application easier to understand, the solution of the present application is described in detail below using the preparation of a lithium-ion battery as a specific embodiment.

[0066] Example 1

[0067] Example 1 is a preparation process of a lithium ion battery. Fig.12 As shown, the specific steps are as follows:

[0068] (1) Preparation of the second fiber fabric by electrospinning

[0069] Preparation of F-BN: Add BN solid to HBF4, stir at 50°C for 12 h, filter, wash with deionized water, and dry to obtain F-BN powder.

[0070] Preparation of electrospinning solution: Dissolve 1g PVDF powder in 10mL N,N-dimethylformamide and stir for 4h to obtain the first electrospinning solution. Dissolve 1g PPC powder in 10mL acetonitrile, add 200-500mg F-BN powder and stir for 4h to obtain the second electrospinning solution.

[0071] Preparation of the second fiber fabric: Electrospinning uses side-by-side needles to inject the second electrospinning solution (PVDF solution) and the second electrospinning solution (PPC+F-BN electrospinning solution) respectively to prepare the second fiber fabric with a side-by-side structure. After electrospinning, the second fiber fabric is removed from the drum and placed in an 80°C forced air oven to dry for 8 hours, then punched into small discs with a diameter of 16 mm and placed in a glove box for standby use.

[0072] (2) Preparation of solid electrolyte

[0073] Weigh the second fiber fabric disc with a mass of m1, and drip the electrolyte with a mass of m2 onto the disc, wherein 10% ≥ m2 / m1 ≥ 5%, to obtain a solid electrolyte. Fig.11 The scanning electron microscope image in FIG. 2 shows that the gel covers the first fiber. The content of the electrolyte in the solid electrolyte can be obtained by thermogravimetric analysis.

[0074] (3) Cathode preparation

[0075] First, weigh 100 mg of PVDF binder and place it in a stirring bottle, add 1 mL of N-methylpyrrolidone, and stir for 1 hour until PVDF is completely dissolved. Then add 100 mg of conductive carbon black Super P and 1 mL of N-methylpyrrolidone, and stir at room temperature for 1 hour. Then add 800 mg of lithium iron phosphate positive electrode active material and 1.5 mL of N-methylpyrrolidone, stir at room temperature for more than 6 hours to obtain positive electrode slurry. Then coat the positive electrode slurry on aluminum foil, dry it at 80°C for more than 6 hours, and then cut it into discs with a diameter of 12 mm to obtain a lithium iron phosphate positive electrode, and place it in a vacuum oven for drying and storage.

[0076] (4) Assembling the battery

[0077] Assemble button cells according to the structure of lithium metal negative electrode, solid electrolyte, and lithium iron phosphate positive electrode. After standing for 2 hours, the performance test can be carried out.

[0078] Example 2-Example 5, Comparative Example 1-Comparative Example 2

[0079] Examples 2-5 and Comparative Examples 1-2 are all lithium-ion batteries, and their preparation process is the same as that of Example 1. After preparation, performance tests are performed. The battery has a cycle rate of 0.5C at 25°C and 200 cycles. The mass ratio of the electrolyte and F-BN, as well as the room temperature ionic conductivity test results of the solid electrolyte and the battery cycle performance results are shown in Table 1.

[0080] Table 1

[0081]

[0082] As can be seen from Table 1, compared with Examples 2 to 5 and Comparative Examples 1 to 2, a reasonable electrolyte ratio can significantly improve the room temperature ionic conductivity of the solid electrolyte and the cycle capacity retention rate of the lithium ion battery. When m2 / m1 is 7% and m(F-BN) / m(PPC) is 30%, the room temperature ionic conductivity of the solid electrolyte is 7.2×10 -4 S / cm, the cycle capacity retention rate of the lithium-ion battery at 25°C and 200 cycles is 98.6%, and the overall performance is relatively excellent.

[0083] Obviously, those skilled in the art can make various changes and modifications to the present application without departing from the spirit and scope of the present application. Thus, if these modifications and variations of the present application fall within the scope of the claims of the present application and their equivalents, the present application is also intended to include these modifications and variations.

Claims

1. A solid electrolyte, characterized in that including a gel and a first fiber fabric; The gel covers the first fiber fabric and fills the pores of the first fiber fabric; The first fiber fabric includes interwoven first fibers, and the gel-forming material includes an electrolyte and second fibers dissolved in the electrolyte; wherein the first fibers include polyvinylidene fluoride fibers, and the second fibers include polypropylene carbonate fibers.

2. The solid electrolyte according to claim 1, characterized in that In the solid electrolyte, the mass of the electrolyte accounts for 5%-10% of the sum of the mass of the first fiber and the second fiber.

3. The solid electrolyte according to claim 1, characterized in that The solid electrolyte further includes fluorinated boron nitride, and the fluorinated boron nitride is dispersed in the gel.

4. The solid electrolyte according to claim 3, characterized in that The mass of the fluorinated boron nitride accounts for 10%-60% of the mass of the second fiber.

5. The solid electrolyte according to claim 1, characterized in that The electrolyte includes a non-aqueous organic solvent, a lithium salt and an additive.

6. The solid electrolyte according to claim 5, characterized in that The non-aqueous organic solvent includes cyclic carbonates and linear carbonates.

7. A method for preparing a solid electrolyte, characterized in that: include: Providing a second fiber fabric, the second fiber fabric comprising first fibers and second fibers interwoven; wherein the first fibers comprise polyvinylidene fluoride fibers, and the second fibers comprise polypropylene carbonate fibers; The electrolyte is dripped onto the second fiber fabric, and the second fibers are dissolved in the electrolyte to form a gel covering the first fibers, thereby obtaining the solid electrolyte.

8. The method for preparing a solid electrolyte according to claim 7, characterized in that: The second fiber fabric is provided, wherein the second fiber fabric includes first fibers and second fibers interwoven together, and the second fiber fabric also includes: The first electrospinning liquid and the second electrospinning liquid are prepared to form the second fiber fabric by adopting an electrostatic spinning process; wherein the first electrospinning liquid includes a polyvinylidene fluoride solution, and the second electrospinning liquid includes a polypropylene carbonate solution.

9. The method for preparing a solid electrolyte according to claim 8, characterized in that: The second electrospinning solution also includes a boron nitride fluoride solution. When the electrolyte is dripped onto the second fiber fabric, the boron nitride fluoride is dispersed in the gel.

10. A solid-state battery, characterized in that: The invention comprises a positive electrode active material, a negative electrode active material and a solid electrolyte as claimed in any one of claims 1 to 6.

Citation Information

Patent Citations

  • Fiber cloth-based lithium ion battery diaphragm as well as preparation method and application thereof

    CN112038542A

  • Polymer gel electrolyte forming thin sheet and its use and manufacturing method thereof

    CN1204132A

  • Porous sheet material for forming macromolecular gel and macromolecular gel electrolyte using this and its manufacturing method

    JP2001118603A

  • Gel electrolyte formable sheet, gel electrolyte support sheet and lithium secondary battery using its sheets

    JP2003068362A

  • Sheet for forming a polymer gelled electrolyte, a polymer gelled electrolyte using it, and a method for manufacture thereof

    US6114068A